1990
DOI: 10.1002/cne.903020313
|View full text |Cite
|
Sign up to set email alerts
|

Location of motor pools innervating chick wing

Abstract: Intramuscular injections of HRP were used to map the spinal cord location of motoneurons innervating wing and shoulder girdle muscles in newly hatched chicks. Motor pools are grouped in the lateral motor column in relationship to embryonic origin of the muscles: muscles derived from the ventral muscle mass are innervated by medially lying motor pools, while muscles derived from the dorsal mass are innervated by lateral pools. Motor pool position is also well correlated with nerve supply. Muscles innervated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 16 publications
5
26
0
Order By: Relevance
“…For these reasons, we studied the European starling, a passerine bird capable of powered flight. This study extends previous studies of the domestic fowl for which: 'a general lack of flightedness in the fowl may influence the details of motor pool organization' [Hollyday and Jacobson, 1990]. The distribution of motoneurons innervating the supracoracoideus in the starling is similar to the distribution described for the domestic fowl in the retrograde degeneration study of Ohmori et al [1982], and the tracer studies of Straznicky and Tay [1983] and Hollyday and Jacobson [1990].…”
Section: Muscle Histochemistrysupporting
confidence: 75%
See 1 more Smart Citation
“…For these reasons, we studied the European starling, a passerine bird capable of powered flight. This study extends previous studies of the domestic fowl for which: 'a general lack of flightedness in the fowl may influence the details of motor pool organization' [Hollyday and Jacobson, 1990]. The distribution of motoneurons innervating the supracoracoideus in the starling is similar to the distribution described for the domestic fowl in the retrograde degeneration study of Ohmori et al [1982], and the tracer studies of Straznicky and Tay [1983] and Hollyday and Jacobson [1990].…”
Section: Muscle Histochemistrysupporting
confidence: 75%
“…pectoralis). Nerve branching patterns can also be a useful starting point for determining muscle homologies [see Goslow et al, 1989] as can the location of motorpools within the spinal cord [Straznicky and Tay, 1983] and developmental studies [Cheng, 1955;Sullivan, 1962;Hollyday and Jacobson, 1990]. For the muscles in this study, homologies were determined using anatomical and developmental evidence (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In the control side of the embryos, spinal nerves 13-16 and a small region of spinal nerve 17 innervate the forelimb (Hollyday and Jacobson, 1990). However, a ~one-segment rostral shift in the spinal nerves that project to the forelimb was observed in the electroporated side (Fig.…”
Section: Expression Of Gdf11 Causes Rostral Displacement Of Motoneuromentioning
confidence: 90%
“…Gutman et al [5] indicated the existence of relationships between locations of muscles and motoneuron pools in axial muscles in chicken. Some investigators [5,6,8,9] concluded that the motoneuron position is correlated with ontogenetic events in chicken. Table 2 shows the cell body diameters (average of maximal and minimal diameters of cells with a visible nucleus) of motoneurons labeled after injections into each of the 6 tail muscles.…”
mentioning
confidence: 99%
“…These muscles are innervated by motoneurones with cell bodies in the spinal cord. Some investigators showed the location of motor pools innervating wing muscles [6,15], hindlimb muscles [14], neck muscles [17], axial muscles [5] and M. sphincter cloacae [13] in the domestic fowl. However, no investigators showed the spinal location of motoneurons innervating tail muscles.…”
mentioning
confidence: 99%